A Novel Model and Infrastructure for Clinical Outcomes Data Collection and Their Systematic Evaluation for UK Patients Receiving Proton Beam Therapy. Issue 1 (January 2022) - Hwang, E.; Burnet, N.G.; Crellin, A.M.; Ahern, V.; Thwaites, D.I.; Gaito, S.; Chang, Y.-C.; Smith, E.
Abstract: Aims: To establish an infrastructure for sustainable, comprehensive data collection and systematic outcomes evaluation for UK patients receiving proton beam therapy (PBT). Materials and methods: A Proton Outcomes Working Group was formed in 2014 to develop a national minimum dataset for PBT patients and to define a clinically integrated informatics solution for data collection. The Christie Proton Beam Therapy Centre formed its Proton Clinical Outcomes Unit in 2018 to collect, curate and analyse outcomes data prospectively for UK-treated patients and retrospectively for UK patients referred abroad for PBT since 2008 via the Proton Overseas Programme (POP). Results: A single electronic form (eForm) was developed to capture the agreed data, using a data tree approach including conditional logic: data items are requested once, further questions depend on previous answers and are sensitive to tumour site and patient pathway time point. Relevant data automatically populate other forms, saving time, prompting completeness of clinical assessments and ensuring data consistency. Completed eForm data populate the electronic patient record and generate individualised outputs, including consultation letters, treatment summary and surveillance plans, based on organs at risk irradiated, age and sex. All data regarding POP-treated patients are verified and migrated into the system, ensuring that patient data, whether overseas or UK treated, are consistently recorded. The eForm utilises a 'user friendly' web portal interface, the Clinical Web Portal, including clickable tables and infographics. Data items are coded to a universally recognised standard comparable with other data systems. Patient-reported outcomes are also integrated, highlighting significant toxicities and prompting a response. Outcomes data can be correlated with dosimetric DICOM data to support radiation dose modelling. Conclusion: Outcomes data from both POP-treated and The Christie-treated patients support long-term care, allow evaluation of PBT efficacy and safety, assist future selection of PBT patients and support hypothesis generation for future clinical trials. Highlights: Inventive data collection methodologies are required for proton beam therapy. The UK's approach to outcomes data collection is key to ensure every patient counts. Electronic forms can be used for tracking outcomes while supporting clinical care. Outcomes data support long-term evaluation of treatment approaches.